Cell Wall Heterogeneity in Root Development of Arabidopsis - Somssich, Marc; Khan, Ghazanfar Abbas; Persson, Staffan (Frontiers in Plant Science, 2016)
Plant cell walls provide stability and protection to plant cells. During growth and development the composition of cell walls changes, but provides enough strength to withstand the turgor of the cells. Hence, cell walls are highly flexible and diverse in nature. These characteristics are important during root growth, as plant roots consist of radial patterns of cells that have diverse functions and that are at different developmental stages along the growth axis. Young stem cell daughters undergo a series of rapid cell divisions, during which new cell walls are formed that are highly dynamic, and that support rapid anisotropic cell expansion. Once the cells have differentiated, the walls of specific cell types need to comply with and support different cell functions. For example, a newly formed root hair needs to be able to break through the surrounding soil, while endodermal cells modify their walls at distinct positions to form Casparian strips between them. Hence, the cell walls are modified and rebuilt while cells transit through different developmental stages. In addition, the cell walls of roots readjust to their environment to support growth and to maximize nutrient uptake. Many of these modifications are likely driven by different developmental and stress signalling pathways. However, our understanding of how such pathways affect cell wall modifications and what enzymes are involved remain largely unknown. In this review we aim to compile data linking cell wall content and re-modelling to developmental stages of root cells, and dissect how root cell walls respond to certain environmental changes.